2021
DOI: 10.1590/1980-220x-reeusp-2020-0476
|View full text |Cite
|
Sign up to set email alerts
|

Association between spirituality and quality of life of women with breast cancer undergoing radiotherapy

Abstract: Objective: To verify whether there is an association between spirituality/religiosity and quality of life of women with breast cancer undergoing radiotherapy. Method: Cross-sectional, quantitative study performed between May and July 2019 in an Oncology Hospital of Porto Alegre state, Brazil. A sociodemographic questionnaire and the instruments EORTC-QLQ-C30 and WHOQOL-SRPB were applied. The data were verified through Shapiro-Wilk test, Pearson correlation coefficient, and Spearman. Results: The sample compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 13 publications
(15 reference statements)
0
13
0
1
Order By: Relevance
“…Special attention should therefore be paid to the spiritual issues of physically debilitated and suffering patients. In support of this, Brandão et al [ 68 ] suggest that high levels of spirituality in patients may lead to better endurance of physical symptoms. Spirituality has been recognized by researchers, clinicians, and patients as an important resource for addressing distress when facing death [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 91%
“…Special attention should therefore be paid to the spiritual issues of physically debilitated and suffering patients. In support of this, Brandão et al [ 68 ] suggest that high levels of spirituality in patients may lead to better endurance of physical symptoms. Spirituality has been recognized by researchers, clinicians, and patients as an important resource for addressing distress when facing death [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 91%
“…Concerning spirituality, 47% of caregivers showed an excellent perception of this dimension, which was the best scored (mean, 21; in a score range between 11 and 28). Similarly, a study conducted in Brazil on women with breast cancer also reported a very high score in the spiritual dimension (mean, 17.8; in a range of 11-20) 15 . According to a literature review carried out in Alberta, Canada, 16 the spirituality represents for caregivers a way of coping that helps them to transcend their fears, make decisions, and assume their caregiving role better.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study conducted in Brazil on women with breast cancer also reported a very high score in the spiritual dimension (mean, 17.8; in a range of 11-20). 15 According to a literature review carried out in Alberta, Canada, 16 the spirituality represents for caregivers a way of coping that helps them to transcend their fears, make decisions, and assume their caregiving role better. Likewise, another study in caregivers of patients with advanced cancer showed that spirituality and religiosity help caregivers cope with their loved ones' disease, and many caregivers reported that spirituality and religiosity had a positive effect on physical and emotional symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with other research that emphasizes the role of spirituality in determining the psychological well-being of people with other diseases. For example, Brandão et al, ( 2021 ) concluded that there is a positive association between spirituality/religiosity and quality of life in women with breast cancer who receive radiotherapy. Likewise, in another study conducted in outpatients with heart failure, greater spiritual well-being, specifically sense of life/peace, was closely related to fewer depressive symptoms and therefore a better perceived quality of life (Bekelman et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%